METAMORFOSA PERMAINAN KIM DARI ARENA PERJUDIAN KE SENI PERTUNJUKAN DI KOTA SOLOK - Arnailis arnailis; Zahara Kamal (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
ABSTRACT This research aims at describing the metamorphose of KIM performance in the context of wedding ceremony in Solok city, Sumatera Barat Province. This research used analysis descriptive method by listing KIM perfor-mances textually and contextually. To See the change of KIM performance, theories used in this research were metamorphose theory and aesthetic theory. Research results showed that today, the games of KIM has be-come a performing art functioning as one of new alternatives in entertainment and as the media of communi-cation to learn Minangkabau language. This performing art is wholly packed in the series of interesting aesthetics because every number released is conveyed through dendang (singing/vocal) with the song rhythms that are famous and trend in today society.